Persekutuan Komanditer yang dibubarkan Dalam Kaitannya Dengan Kegiatan Perbankan - Prima Maria Fatima Bana; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2021)
The development of business in the community requires the entity of a business entity to ensure legal certainty in doing business. One entity that is always in demand by the public is a limited partnership or commanditaire vennootschap (CV). Limited partnership is a business entity that requires a bank financial institution to conduct transactions in the financial sector. In a limited partnership, two actions will be taken, namely the freezing of the limited partnership or the dissolution of the limited partnership if it does not achieve the goals and objectives or does not achieve profits. In the description above, there isalso the formulation of the problem (1) How is the arrangement of limited partnership dissolved in relation to banking activities? (2) What are the legal consequences of the disbanded limited partnership on banking activities in relation to third parties? This research uses normative research methods based on expert opinion, literature and legislation. The author has analyzed a court decision where the limited partnership which has been dissolved but still has problems with the banking sector that must be resolved and the case contains elements of ne bis in idem so that the court's decision does not accept the lawsuit.